Teaching applications of mathematics: The effect of the intervention on the participating teachers - Abdallah ASLI; Iuliana ZSOLDOS-MARCHIS (Studia Universitatis Babes-Bolyai, 2023)
The purpose of this study is to examine the effect of the intervention with teaching applications of mathematics in other disciplines on teachers` attitudes towards teaching applications of mathematics. The research was conducted in the 2021-2022 school year in Israel and a two-groups pretest-posttest quasi-experimental research design was used. The participants were four classes (two of them are 11th grades and two are 12th grades) with four teachers at Al-Bukhari High School in Arraba city in northern Israel. The research instruments were three interview guides. The first interview was conducted before the intervention with all the 4 teachers and it contained 16 questions about their attitudes toward teaching mathematics and applications of mathematics. The second and third interview was similar and it was conducted during respectively after the intervention with the teachers in the experimental group. These interviews contained 5 questions related to teaching applications of mathematics in other disciplines. The results of the study showed that teaching applications of mathematics in other disciplines has a positive effect on teachers. Before the intervention, the teachers taught using the standard method, and they rarely taught applications. The teachers were not qualified enough to teach applications of mathematics and were not aware of the advantages of teaching applications of mathematics. By the intervention teachers were exposed to the inclusion of applications in teaching mathematics, and their attitudes towards teaching applications of mathematics improved and their level of confidence to teach applications increased significantly (increased from 7 to 9 on a scale from 1 to 10). That means, the intervention helped the teachers to teach the applications of mathematics successfully and with self-confidence. Furthermore, despite the difficulties and the obstacles in teaching applications of mathematics in other disciplines, teachers liked to teach the applications of mathematics and were satisfied with the results and the change among the students. They reported that they would implement the teaching applications of mathematics in other disciplines in all classes that they teach and would recommend it to their fellow teachers.